The Figurative Language of the Indigenous Semai People of Lembah Jelai, Malaysia - Hassan Abdul, Abu; Rasdi Saamah, Mohd.; Ayob, Razali; Twahir, Wahibah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
This study aims to examine aspects of the figurative language of a sub-group of the Orang Asli of Malaysia, namely the Semai people, living in Lembah Jelai, Pahang, Malaysia. This qualitative study was based on a semi-structured interview method involving five native speakers of the Semai language. The researchers used an adapted version of the cognitive-linguistic framework of Lakoff and Johnson (1980) to analyze the interview data. The findings showed that most of the figurative expressions used in their language were primarily based on natural and cultural elements that heavily influenced the way they led their lives. In particular, the findings showed that the Semai community used figurative expressions in their conversations not only to articulate their feelings and thoughts but also to serve as unwritten social guidelines. Overall, these findings indicate that indigenous communities living in far remote areas in jungles use figurative languages to guide their peoples in forging close kinships, in cementing strong societal bonds, and in dealing with the spiritual realm. The findings also provide greater insight into the understanding of the uniqueness of the figurative language of the Semai community, which is considered as a sub-language of the mainstream Malay language in the Malay Archipelago. Surely, such a language needs to be persevered to ensure it will continue to thrive among the younger generation of the Semai people, given its significant influence on the development of their emotions, thinking, and culture